Regulation of inflammatory biomarkers by intravenous methylprednisolone in pediatric ARDS patients: Results from a double-blind, placebo-controlled randomized pilot trial. (January 2016) - Schwingshackl, Andreas; Kimura, Dai; Rovnaghi, Cynthia R.; Saravia, Jordy S.; Cormier, Stephania A.; Teng, Bin; West, Alina N.; Meduri, Umberto G.; Anand, Kanwaljeet J.S.
Highlights: Low-dose steroid therapy in PARDS is feasible and may improve ventilation and oxygenation. The molecular mechanisms underlying potential changes in these outcomes remained unclear. This study examines the effects of IV methylprednisolone on plasma biomarkers of PARDS. We simultaneously measured cytokines, cell counts and coagulation parameters in PARDS. We report statistical models useful for future RCTs to predict ARDS severity and outcomes. Abstract: Objective: A double-blind, randomized controlled trial showed that low-dose glucocorticoid therapy in pediatric ARDS patients is feasible and may improve both ventilation and oxygenation indices in these patients. However, the molecular mechanisms underlying potential changes in outcomes remain unclear. Based on these clinical findings, this study was designed to examine the effects of intravenous methylprednisolone on circulating inflammatory biomarkers in pediatric ARDS patients. Design: Double-blind, placebo-controlled randomized trial with blood collection on study entry and day 7. Setting: Tertiary care children's hospital. Patients: Children (0–18 years) with ARDS undergoing mechanical ventilation. Interventions: 35 children were randomized within 72 h of mechanical ventilation. The glucocorticoid group received methylprednisolone 2 mg/kg loading dose followed by 1 mg/kg/day continuous infusion from days 1 to 7. Both groups were ventilated following the ARDSnet recommendations. WBC and differential cell counts, plasma cytokines and CRP levels, and coagulation parameters were analyzed on days 0 and 7. Results: At study entry, the placebo group had higher IL-15 and basophil levels. On day 7, in comparison to study entry, the placebo group had lower IL-1α, IFN-γ and IL-10 levels. The glucocorticoid group had lower INF-α, IL-6, IL-10, MCP-1, G-CSF and GM-CSF levels, and higher IL-17α levels on day 7 in comparison to study entry. Total and differential cell counts remained unchanged within the placebo group between days 0 and 7, whereas in the glucocorticoid group total WBC and platelets counts were increased on day 7. Pearson's correlation studies within the placebo and glucocorticoid groups revealed positive and negative correlations between cytokine levels, cell counts, coagulation parameters and relevant clinical parameters of disease severity identified in our previous study. Multiple regression models identified several cytokines as predictors for alterations in clinical parameters of disease severity. Conclusion: This pilot study shows the feasibility of simultaneously measuring multiple inflammatory cytokines, cell counts and coagulation parameters in pediatric ARDS patients. We report statistical models that may be useful for future, larger trials to predict ARDS severity and outcomes.